Foot drop: The first sign of an intracranial tumor? - (:unkn) unknown (CHURCHILL LIVINGSTONE, 2007)
Isolated foot drop due to a brain lesion is rare. A 48-year-old man complained of inability to dorsiflex the right foot. Right dorsiflexion had 015 muscle strength and there were no upper neuron findings on his neurological examination. Magnetic resonance imaging of the brain revealed a left parasagittal brain mass. The lesion was removed and muscle activity returned with 3/5 muscle strength 6 weeks after the operation. The parasagittal area is located at the foot of the homunculus. Therefore, in patients with foot drop, lesions of the parasagittal area should be considered. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: foot drop; parasagittal brain lesion; DIFFERENTIAL-DIAGNOSIS